Do gasoline prices converge in a unified Europe with non-harmonized tax rates? - Axel Dreher; Tim Krieger (ETH Zurich, KOF Swiss Economic Institute, 2005)
The paper presents univariate and panel unit root tests for gasoline and oil price convergence over the last decade. We test for the absolute versus relative version of the law of one price (LOOP) and estimate the speed of convergence as well as its development over time. Our results show that the absolute version of the LOOP cannot be supported. Constant price differences between countries remain, caused mainly by existing tax differences. The relative version of the LOOP is strongly supported by the data. The speed of convergence increased over time, but differs for gross and net-of-tax prices. We can show that national tax policy by EU member states is not (yet) threatened by arbitrage due to cross-border shopping.
Keywords: H7; F15; Q48; C2; 330; price convergence; law of one price; gasoline; international taxation; European integration; panel unit roots; Benzin; Preis; Internationaler Preiszusammenhang; Mineralölsteuer; EU-Staaten